2004
DOI: 10.1242/jcs.01116
|View full text |Cite
|
Sign up to set email alerts
|

The sequences appended to the amyloid core region of the HET-s prion protein determine higher-order aggregate organization in vivo

Abstract: The [Het-s] prion of the fungus Podospora anserina propagates as a self-perpetuating amyloid form of the HET-s protein. This protein triggers a cell death reaction termed heterokaryon incompatibility when interacting with the HET-S protein, an allelic variant of HET-s. HET-s displays two distinct domains, a N-terminal globular domain and a C-terminal unstructured prion-forming domain (residues 218-289). Here, we describe the characterization of HET-s(157-289), a truncated form of HET-s bearing an extensive del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 27 publications
0
63
0
1
Order By: Relevance
“…Plasmids-Construction of Escherichia coli expression plasmids for C-terminally histidine-tagged versions of both polypeptides has been described (6,15). In brief, the reading frame of HET-s-(218 -289) and HET-s-(157-289) was amplified by PCR and cloned into pET-21a using NdeI and HindIII restriction sites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmids-Construction of Escherichia coli expression plasmids for C-terminally histidine-tagged versions of both polypeptides has been described (6,15). In brief, the reading frame of HET-s-(218 -289) and HET-s-(157-289) was amplified by PCR and cloned into pET-21a using NdeI and HindIII restriction sites.…”
Section: Methodsmentioning
confidence: 99%
“…When expressed in P. anserina, the HET-s prion domain alone can propagate the prion, but is not functional in heterokaryon incompatibility. To restore this function, at least parts of its N-terminal domain are needed (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Red lines encircle cross-peaks that show a virtually complete loss of intensity after t = 6 weeks. c,d, Homonuclear 13 ex C-13 C DREAM correlation spectra of 13 C, 15 N-labeled, HETs(218-289) fibrils. The carbonyl region of the DREAM spectra (c) was recorded at 40 kHz MAS.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Are Infectious-The proteinase K-resistant amyloid core of HET-s amyloids corresponds to the region spanning residue 218 -289 (22,38). We have previously shown that HET-s fibrils submitted to proteinase K digestion retain infectivity (21).…”
Section: Amyloids Of Het-s-(218 -289)mentioning
confidence: 99%